Physicochemical Properties and Fatty Acid Methyl Ester (FAME) Extract of Maggot Black Soldier Fly (Hermetia illucens) as Animal Feed - Risalatul Fathimah; Dika Putra Wijaya; Amirotul Muniroh; Sumari Sumari; Danar Danar; Nilna Inayatan Nafiah; Fatimah Az-Zahra; Aura Gitta Zhafirah; Grestya Dienda Monicha; Marendha Salma Sajidah; Juwita Oktaviani; Fina Kharisma Musallamah; Putri Rizky Febrianti (Biology, Medicine, & Natural Product Chemistry, 2026)
This study aimed to evaluate the physicochemical properties and fatty acid methyl ester (FAME) profile of Hermetia illucens (BSF) maggot extract as a potential sustainable ingredient for animal feed. Lipid extraction was performed using a modified Bligh and Dyer method by substituting chloroform with n-hexane to ensure safer and environmentally friendly processing. Proximate analysis revealed that BSF maggots contained 29.36% crude protein, 43.76% crude fat, 9.27% ash, 19.94% crude fiber, and a low moisture content of 3.06%, indicating high nutritional density and storage stability. XRF and qualitative tests confirmed significant mineral content, particularly CaO, K?O, and P?O?, with no detectable heavy metals or harmful contaminants, supporting their safety for feed applications. Microscopic analysis showed particle sizes ranging from 2,000-10,000 nm, classifying the material as a nanostructured biomass. The FAME profile demonstrated a diverse composition dominated by 9-octadecenoic acid (10.92%), triacontane (8.87%), octadecanoic acid (7.65%), and heptacosanoic acid (7.17%). Key medium- and long-chain fatty acids such as dodecanoic acid (C12:0), elaidic acid (C18:1), and stearic acid (C18:0) were also detected, indicating the suitability of BSF lipids as an energy-dense feed component with oxidative stability. Overall, the biochemical and structural characteristics obtained in this study highlight BSF maggots as a promising, nutrient-rich, and environmentally sustainable ingredient for animal feed formulations.